Contingency-testing in the use of the sentence acceptability task by Ho (2019) in understanding dyslexia in Singapore : an EEG study - Tan, Priscilla Le En (Nanyang Technological University, 2020)
Morphological awareness is known to explain variance in word reading and reading comprehension within groups of people with reading difficulties and those who have typical reading ability. It has been argued to be particularly vital in reading Chinese, where differences in meaning can arise from intra-word (that is, constituent character) manipulation. This present study investigated the robustness of Ho (2019)’s Sentence Acceptability Task in investigating morphological processing performance and the N400 component in children with Chinese language-specific dyslexia in comparison with non-dyslexic adults using electroencephalography (EEG). 25 English-Chinese bilinguals of different Chinese proficiency levels were recruited into the present study and compared with Ho (2019)’s child dataset. Despite such apparent dissimilarity, no main effect of either task experimental condition or participant group across reaction time, accuracy and mean N400 amplitude was found, calling the Sentence Acceptability Task’s robustness into question. Within-groups comparisons revealed no significant differences within the child dataset, but a main effect of location (anteriority/posteriority) on N400 amplitude was found within the adult sample. Curiously, an inverse relationship between proficiency and N400 amplitude was observed across adult Chinese proficiency levels, where other studies have found the opposite. Nevertheless, alternative explanations for lack of significant main and interaction effects, such as children forming response strategies and development-related changes to the N400 component are offered, suggestions for further refinement of the Sentence Acceptability Task are made, and future directions of this line of research are discussed.